TEACHERS AND STUDENTS PERCEPTIONS OF INTERNATIONALISATION OF HIGHER EDUCATION IN NIGERIA - Blessing. F. Adeoye; Blessing E. Anyikwa; Deneca W. Avant (European Scientific Journal, ESJ, 2012)
This study seeks to address the gap in literature supporting internationalization of higher education by exploring the perceptions of teachers and students in Nigeria. Four hundred and forty six participants were involved in the study. Descriptive statistics was used to describe the profile and distribution of the sample population, the motivational factors and the perceptions of participants. Eighty four percent of the participants admitted that internationalization of higher education promotes collaboration among students and lecturers, 80% indicated that it exposes students to online programme and other international opportunities. Also, 81% admitted that internationalization of higher education will expand academic/research horizon of a practicing institutions in Africa while the remaining of the respondents disagreed with such notion. Majority indicated lack of awareness of guiding policies on internationalization of higher institutions in Africa, and that it is not part of African government foreign policies. The participants also indicated that there is no national framework for monitoring and evaluation of internationalization of higher education in Africa. They pointed out some barriers/challenges of internationalization of higher education across Africa.